Older, self-identifying gay men's conceptualisations of psychological well-being (PWB): A Canadian perspective - Handlovsky, Ingrid (Nursing philosophy, 2024)
Many older gay men experience diminished psychological well-being (PWB) due to unique circumstances including discrimination, living with HIV, and aging through the HIV/AIDS crisis. However, there remains ambiguity as to how older gay men define and understand PWB. Our team interviewed and analyzed the accounts of 26 older (50+) self-identifying English-speaking men living in southwestern British Columbia, Canada. We drew on tenets of constructivist grounded theory and intersectionality to account for unique contextual considerations and power relations. Semi-structured Zoom interviews were conducted from August-October 2022. Interview transcripts were compared to generate high-order conceptual findings underpinned by processes understood as central to PWB. Three PWB temporal processes highlighted interlocking social and contextual circumstances intersecting with power and maturation: (1) being emotionally balanced, (2) living gratitude (3) and fully embracing self-acceptance. Being emotionally balanced supported the affective and sustainable state of contentment, living gratitude drew from the wisdom of accrued experiences to cultivate a positive affective state inclusive to recognising social location privileges, whilst fully embracing self-acceptance redressed the harms of anti-gay discourses that men endured throughout their lives. The knowledge is relevant to service and resource development to deliver tailored PWB supports to older gay men.